2000
DOI: 10.1002/1098-0997(2000)8:5<220::aid-idog1022>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine infection and spontaneous midgestation abortion: Is the spectrum of microorganisms similar to that in preterm labor?

Abstract: Objective: To determine whether microorganisms associated with intrauterine infection and preterm labor play a contributing role in midgestation abortion.Methods: A 4 year retrospective review of spontaneous midgestation abortions for which autopsy and microbiological cultures of placental and fetal tissue were performed was conducted for a tertiary obstetrics hospital, which included a regional referral service for perinatal and fetal pathology. One hundred twenty-nine spontaneously delivered, nonmacerated, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 17 publications
0
32
1
1
Order By: Relevance
“…Embora a colonização por EGB seja citada na literatura como causa de abortamento entre as mulheres 22 , este estudo encontrou que a prevalência de EGB foi duas vezes maior nas mulheres sem história de aborto espontâneo prévio.…”
Section: Discussionunclassified
“…Embora a colonização por EGB seja citada na literatura como causa de abortamento entre as mulheres 22 , este estudo encontrou que a prevalência de EGB foi duas vezes maior nas mulheres sem história de aborto espontâneo prévio.…”
Section: Discussionunclassified
“…Such an undesirable result might occur if the placenta fails at its filtering/removal function and lets microorganisms survive and invade feta tissues. 30 Indeed, one could argue that the higher levels of bacterial isolation from vaginally delivered placentas simply indicate that the fetus senses a hostile microbiologic environment and signals the host in such a way as to escape from this environment. 31 Because the normal route of delivery is through the birth canal, the delivered fetus requires some rudimentary protection in place as it passes through an area containing large numbers of microorganisms.…”
Section: Commentmentioning
confidence: 99%
“…McDonald and Chambers [37] stated that GBS was a key pathogen in unsuspected intrauterine infections underlying spontaneous midgestation abortions. The study of Daugaard et al [38] demonstrated an association between the occurrence of group B Streptococci in the urine and cervix and late spontaneous abortions, but El Kersh et al [24] found no correlation with a history of repeated spontaneous miscarriages.…”
Section: Commentmentioning
confidence: 99%